KHIMAR DAN HUKUM MEMAKAINYA DALAM PEMIKIRAN M. QURAISH SHIHAB DAN BUYA HAMKA - Rizki, Wahyu Fahrul (UIN Sunan Kalijaga Yogyakarta, 2017)
This paper is motivated by the opinion M. Quraish Shihab in his Tafsir Al-Misbah who do not require a Muslim woman wearing Khimar, this opinion is getting a variety of conflicting reactions among the interpreters of Indonesia, one of which is Buya HAMKA. What needs to be answered in this research is how the views of Buya HAMKA and M. Quraish Shihab about the meaning of Khimar? How did the views of Buya HAMKA and M. Quraish Shihab regarding the law of using Khimar? And how are the methods used by Buya HAMKA and M. Quraish Shihab in establishing the law using Khimar?Tafsir Ahkam Method with a comparative study between the two opinions of the character in this study implies that both interpreters have similarities and differences associated with the Khimar. Their equation is in defining the meaning of the word Khimar, ie the headgear, although both give the same definition of Khimar. While the difference between the two is in concluding the law of using Khimar. Buya HAMKA said that a Muslim woman must wear Khimar, while M. Quraish Shihab said that a Muslim woman is not obliged to wear Khimar. The method used by Buya HAMKA in establishing the law using Khimar is the Tafsir Riwayah and Dirayah method. While M. Quraish Shihab using the method of tafsir maudhu'i (thematic).